O związkach kiczu i perswazji - Dąbrowska, Dorota (Załącznik Kulturoznawczy, 2023)
This paper deals with the Kundera’s most popular novel as a passionate dialogue with kitsch. The Unbearable Lightness of Being is based on the antinomy of lightness and heaviness, as well as kitsch and individuality. The narrator treats his characters as the experimental ego and confronts them with the reality created on the cross-scheme of those key-words mentioned above. Kundera interprets the phenomenon of Kitsch as the tool to create a totalitarian reality and slave human beings, but also as something, that can be recognize and ‘domesticate’, and then comprise an inalienable part of human existence and its relation to the world. Paper also deals with the Kundera’s famous aversion to film his novels. He banned any further film adaptations of his work, having disliked the way The Unbearable Lightness of Being had been adapted by Philip Kaufman in 1988.